Optimal capacitor placement in RDS using combined fuzzy & novel power loss sensitivity method - Babu P.V.; Singh S.P. (My University, 2025)
This paper presents a new methodology for optimal capacitor placement problem in Radial Distribution System (RDS) in order to reduce the total power losses, to improve the voltage profile, to enhance voltage stability, and to achieve more energy savings. The main contribution of this paper is (i) fuzzy expert system (FES) is used to find the optimal locations for capacitor placement, (ii) A novel power loss sensitivity method is applied to determine the optimal capacitor size, (iii) Impact of capacitor placement on the system performance of the radial distribution systems is evaluated in terms of voltage profile, power losses, energy savings & voltage stability index (VSI), (iv) the annual cost of energy loss, total annual cost and net savings. The combined fuzzy & novel power loss sensitivity method is implemented on Existing rural 15 bus system and standard IEEE-34 bus distribution system, and the results are compared with an existing PSO method and Fuzzy-Harmony search algorithm (HSA). © 2016 IEEE.